Arduino-Based Moringa Cultivation and Innovation in Processed Moringa Products to Prevent Stunting, Cangkring Village, Jenggawah District, Jember Regency - Saputra, Ramadani Dwi; Afidah, Zidan; Syahputra, Dylanatha Syahputra; Ardiansyah R, Maulana; Maulida, Zulfa; Nuraini, Lailatul (Unram Journal of Community Service, 2024)
The industrial era 4.0 is a new phase in the development of technology in agriculture. Technologies such as drones, sensors, cloud computing, and agricultural automation are examples of the use of the Internet of Things (IoT) as technological advances in agriculture. Moringa is rich in beneficial nutrients, especially for pregnant and lactating mothers so that it can prevent stunting. Internet of Things (IoT) technology is applied to monitor the growth conditions of Moringa in real time, increasing harvest yields in terms of quality and quantity. This program has proven effective in increasing the understanding of the Cangkring village community and can be used as a way to prevent stunting, as well as improve the quality of life in areas with a high prevalence of stunting